Concurrent Hiatal Hernia, Gastric Polyp, and Lupus Nephritis in an Adolescent: A Case Report - Yugatama, Andyan; Yusri Dianne Jurnalis; M. Iqbal Rivai; Irwan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: The coexistence of hiatal hernia (HH), gastric polyp, and lupus nephritis in an adolescent patient presents a unique clinical challenge, demanding a multidisciplinary approach to diagnosis and management. This case report aims to highlight the complexities involved in addressing these concurrent conditions and their implications for patient care. Case presentation: A 16-year-old girl with a history of systemic lupus erythematosus (SLE) and lupus nephritis presented with recurrent abdominal pain. Esophagogastroduodenoscopy (EGD) revealed a hiatal hernia and an esophageal polyp. The patient underwent laparoscopic gastrofundoplication for the hiatal hernia, and the polyp was subsequently removed via polypectomy. Histopathological examination confirmed a hyperplastic gastric polyp. The patient's postoperative course was complicated by electrolyte imbalances and dysphagia, which were managed successfully. Conclusion: This case underscores the importance of a thorough diagnostic workup in adolescents with SLE presenting with gastrointestinal symptoms. The concurrent presence of HH, gastric polyp, and lupus nephritis necessitates a multidisciplinary approach involving gastroenterologists, surgeons, rheumatologists, and other specialists. Careful attention to potential complications, such as electrolyte imbalances and dysphagia, is crucial for optimal patient outcomes.